Cyclic experimental and numerical analytical investigation of precast concrete frames with buckling-restrained braces considering various assembling connections. (December 2021) - Li, Beibei; Wang, Jingfeng; Duan, Mengjun; Guo, Lei; Wang, Bo
Abstract: Buckling-restrained braces (BRBs) are able to provide good lateral stiffness and energy dissipation capability for precast concrete (PC) frames under the earthquake. However, there is little research on the reliable connection between BRBs and PC frames with different beam-column assembling joints. To investigate cyclic response and failure modes of PC frames with BRBs, cyclic loading tests of four PC frames with BRBs and one bare reinforced concrete (RC) frame were conducted in this paper. Two types of beam-column assembling joints, i.e. the integral type and the concealed corbel type, were designed to check their connection reliability. Moreover, three novel connection types between BRBs and PC frames, i.e. the end plate connection type, the column-only connection type and the splicing connection type, were developed to explore their cooperative working performance under lateral cyclic loading. The experimental phenomena and failure features were observed and recorded. The hysteretic and skeleton curves, ductility coefficients, stiffness degradation and energy dissipation capacity of the structure were compared and analyzed. It indicated that the bearing capacity and failure modes of specimens are close to each other when the two reasonable beam-column assembly joints were adopted. Meanwhile, specimens with different BRB-PC frame connection types exhibited similar seismic performance. It demonstrated that the BRBs could effectively enhance the seismic performance of PC frames in comparison with the bare counterpart. Furthermore, the finite element (FE) model was established and verified by the test results. Then the parametric analysis, including load, material, and geometric parameters, was performed systematically. The above research results could be contributed to promoting the design and application of BRBs in PC frames.